2019
DOI: 10.15845/bjclcj.v7i1.2879
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Insanity, Psychosis and Impaired Reality Testing in Norwegian Law

Abstract: How mental disorder relates to criminal insanity is a contested matter. Norway has a tradition of using a ‘medical model’ for the definition of criminal insanity that is unique in an international perspective. According to this model, insanity is determined only in relation to a medical criterion, so that all that is required is the presence of a qualifying mental disorder. Criminal insanity is, under the current rule, equated with psychosis, although this rule has recently been subject to a law reform. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…This could improve understanding of how a legal principle affects clinical examinations and descriptions. The legal principle for legal insanity in Norway changed after we selected the reports for this study [ 10 , 12 ]. To replicate this study using reports written after this change may provide important insight into whether changes in the rule of law affect the clinical practice of forensic experts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This could improve understanding of how a legal principle affects clinical examinations and descriptions. The legal principle for legal insanity in Norway changed after we selected the reports for this study [ 10 , 12 ]. To replicate this study using reports written after this change may provide important insight into whether changes in the rule of law affect the clinical practice of forensic experts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it would be interesting to know more about which information the judges refer to in their verdicts when presented with forensic witnesses’ reports and oral statements in court. Investigations have shown that courts usually follow the experts’ conclusions in their verdicts [ 10 ]. The experts’ reporting of symptom descriptions from collateral sources could be studied if the researchers recorded which symptoms they found in these sources and compared them with the experts’ descriptions in the reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the clinical construct “psychotic”, the legal construct is, for all practical purposes, equivalent to the construct “legally insane”, and we use the latter term in this paper to ensure its differentiation from the clinical term. To be evaluated as legally insane, a defendant must have psychotic symptoms of a certain severity and some functional impairment at the time of the crime, but no connection needed to be established with the offense committed as Norway held the biological / medical principle 1 [ 13 – 15 ]. The legal construct of severe mental retardation involved intellectual impairment, which could be caused by clinical mental retardation or by other conditions, such as acquired brain damage.…”
Section: Introductionmentioning
confidence: 99%